Engineered Exosomes as a Photosensitizer Delivery Platform for Cancer Photodynamic Therapy - Dao A.; Kushwaha R.; Kumar A.; Huang H.; Banerjee S. (My University, 2025)
Photodynamic therapy (PDT), a non-/minimally invasive cancer treatment method, has the advantages of low side effects, high selectivity, and low drug resistance. It is currently a popular cancer treatment method. However, given the shortcomings of photosensitizers such as poor photostability, poor water solubility, and short half-life in vivo when used alone, the development of photosensitizer nano-delivery platforms has always been a research hotspot to overcome these shortcomings. In the human body, various types of cells generally release bilayer extracellular vesicles known as exosomes. Compared with traditional materials, exosomes are currently an ideal drug delivery platform due to their homology, low immunogenicity, easy modification, high biocompatibility, and natural carrying capacity. Therefore, in this concept, we focus on the research status and prospects of engineered exosome-based photosensitizer nano-delivery platforms in cancer PDT. © 2022 Wiley-VCH GmbH.